Fair value accounting and the cost of equity capital of Asian banks - Ashwag Dignah,; Radziah Abdul Latiff,; Zulkefly Abdul Karim,; Aisyah Abdul-Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The cost of equity is a measure of the required return by investors. It is desirable for firms, especially banks, to lower the cost of equity. There are a number of factors related to the quality of information disclosed that could influence the cost of equity. The accounting regulators aim to improve the quality of information by requiring assets to be valued at fair value. However the application of fair value accounting potentially increases information asymmetry, especially if fair value is estimated and subjected to the judgment of the preparers of financial statements. This asymmetric information problem potentially lowers the information quality and increases investors’ estimation risk and thus influences the cost of equity capital. Therefore, this research investigates the effect of fair value accounting on the cost of equity capital for a sample of Asian banks since banks hold a relatively larger proportion of assets at fair value. Using the generalized method of moment model for dynamic panel data, this research finds significant and positive relationship between assets at fair value and the cost of equity. The results found are similar for both quoted and unquoted assets. Thus although to regulators, fair value accounting provide relevant and timely information to investors, assets at fair value are perceived to be risky and as a consequence investors require higher returns.